Tumor Microenvironment Modifications Recorded With IVIM Perfusion Analysis and DCE-MRI After Neoadjuvant Radiotherapy: A Preclinical Study - Lallemand, François; Leroi, Natacha; Blacher, Silvia; Bahri, Mohamed Ali; Balteau, Evelyne; Coucke, Philippe; Noël, Agnès; Plenevaux, Alain; Martinive, Philippe (Frontiers in Oncology, 2021)
Purpose: Neoadjuvant radiotherapy (NeoRT) improves tumor local control and facilitates tumor resection in many cancers. Some clinical studies demonstrated that both timing of surgery and RT schedule influence tumor dissemination. Previously, Leroi et al, developed a pre-clinical model demonstrating the impact of NeoRT schedule and timing of surgery on the metastatic spreading. We here investigated the impact on tumor microenvironment by functional MRI. Methods: MDA-MB 231 cells were implanted in the flank of SCID mice. Tumors were locally irradiated with 2x5Gy and then surgically removed at different time points after RT. Diffusion-weighted (DW) and Dynamic contrast enhancement (DCE) MRI images were acquired before RT and every 2 days between RT and surgery. IntraVoxel Incoherent Motion analysis was used to obtain information on intravascular diffusion, related to perfusion (F: perfusion factor) and subsequently tumor vessels perfusion. For DCE-MRI, we performed semi-quantitative analyses. Results: In this experimental model, a significant and transient increase of the perfusion factor F (50% of the basal value (n=16, p<0.005)) was observed on day 6 after irradiation as well as a significant increase of the WashinSlope with DCE-MRI at day 6 (n=13, p<0.05). Using immunohistochemistry, an increase of perfused vessels was highlighted, reflecting to the increase of perfusion in MRI at this same time point. Moreover, Tumor surgical resection during this peak of vascularization resulted in an increase of metastasis burden (n=10, p<0.05). Conclusion: Significant differences in perfusion-related parameters were observed on day 6 in a neoadjuvant RT model using SCID mice. These modifications correlated with an increase of perfused vessels in histological analysis and also with an increase of metastasis spreading after the surgical procedure. Those experimental findings are worth considering to design more personalized treatment, by modulating the time of surgery guided on MRI functional data, especially tumor perfusion.